IMPLEMENTASI PROGRAM EDUKASI AIR BERSIH UNTUK MENINGKATKAN KESADARAN LINGKUNGAN SISWA SEKOLAH DASAR - Muhammad Hakiem Sedo Putra; Ayu, Mutiara (Universitas Islam Negeri Raden Intan Lampung, 2026)
Clean water is a vital resource that plays an essential role in maintaining human health and sustaining life. However, low awareness of wise water use remains a common problem, including among elementary school children. This community service program aimed to improve students’ knowledge, awareness, and water-saving behavior through a clean water education program. The activity was conducted at SD Negeri 2 Margadadi, South Lampung Regency, involving 60 students from grades III, IV, and V. The program was implemented using interactive counseling, educational media, educational games, and hands-on practice. Qualitative evaluation was carried out through observation, question-and-answer sessions, and simple quizzes administered before and after the activity. The results indicated an improvement in students’ understanding of the functions and benefits of water, sources of clean water, and water-saving behavior in daily life. The program proved effective in fostering environmental awareness from an early age and has the potential to contribute to sustainable water resource management in the long term.